2021
DOI: 10.1038/s41598-021-89668-5
|View full text |Cite
|
Sign up to set email alerts
|

A screen of FDA-approved drugs identifies inhibitors of protein tyrosine phosphatase 4A3 (PTP4A3 or PRL-3)

Abstract: Protein tyrosine phosphatase 4A3 (PTP4A3 or PRL-3) is highly expressed in a variety of cancers, where it promotes tumor cell migration and metastasis leading to poor prognosis. Despite its clinical significance, small molecule inhibitors of PRL-3 are lacking. Here, we screened 1443 FDA-approved drugs for their ability to inhibit the activity of the PRL phosphatase family. We identified five specific inhibitors for PRL-3 as well as one selective inhibitor of PRL-2. Additionally, we found nine drugs that broadly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The pSKB3 plasmid is a derivative of the pET-28b vector, replacing the thrombin cleavage site with a tobacco etch virus (TEV) protease cleavage site and was a gift from Dr. Konstantin Korotkov at the University of Kentucky . Full-length human PRL-(1, 2, or 3) cDNA or HA-CBS was cloned into the pSKB3 vector using the NheI and XhoI restriction sites via T4 ligase . The HA-CBS construct was obtained from a full-length CNNM3 CBS domain-pair (residues Y301-D451, RefSeq NM_017623.5) gBlock Gene Fragment (IDT), with a human influenza hemagglutinin epitope tag fused to the N-terminus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pSKB3 plasmid is a derivative of the pET-28b vector, replacing the thrombin cleavage site with a tobacco etch virus (TEV) protease cleavage site and was a gift from Dr. Konstantin Korotkov at the University of Kentucky . Full-length human PRL-(1, 2, or 3) cDNA or HA-CBS was cloned into the pSKB3 vector using the NheI and XhoI restriction sites via T4 ligase . The HA-CBS construct was obtained from a full-length CNNM3 CBS domain-pair (residues Y301-D451, RefSeq NM_017623.5) gBlock Gene Fragment (IDT), with a human influenza hemagglutinin epitope tag fused to the N-terminus.…”
Section: Methodsmentioning
confidence: 99%
“… 51 Full-length human PRL-(1, 2, or 3) cDNA or HA-CBS was cloned into the pSKB3 vector using the NheI and XhoI restriction sites via T4 ligase. 52 The HA-CBS construct was obtained from a full-length CNNM3 CBS domain-pair (residues Y301-D451, RefSeq NM_017623.5) gBlock Gene Fragment (IDT), with a human influenza hemagglutinin epitope tag fused to the N-terminus.…”
Section: Methodsmentioning
confidence: 99%
“…Much work on PRL3 inhibitors has focused on computationally screening small molecule libraries to identify potential lead compounds for further in vitro validation and optimization [45,49,77,141,[144][145][146][147][148][149]155]. Rhodanine-based compounds have been of key interest after this chemotype was shown to have inhibitory activity against PRL3 through a high throughput screening of a chemical library in 2006 [141].…”
Section: Small Molecule Inhibitors Against Intracellular Prl3mentioning
confidence: 99%
“… 18 , 19 In preclinical studies, PRL3 has been shown to play a limited role in specification of neural crest progenitors 20 and regulates cellular migration in embryonic kidneys without affecting cell viability. 21 , 22 Therefore, we hypothesize that PRL3 may likewise be expressed in a highly specific manner in developmental cancers, facilitating safe application of PRL3-zumab in these diseases. However, PRL3 expression in the developing tissues of children and its toxicity profile in pediatric patients have not yet been described.…”
Section: Introductionmentioning
confidence: 99%